2020
DOI: 10.1101/2020.04.16.045690
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The scRNA-seq expression profiling of the receptor ACE2 and the cellular protease TMPRSS2 reveals human organs susceptible to COVID-19 infection

Abstract: SummaryBackgroundCOVID-19 caused by SARA-CoV-2 is a disaster sweeping over 200 countries, and more than 2,150,000 people are suffering from the disease and 140,000 people died. ACE2 is a receptor protein of SARS- CoV-2, and TMPRSS2 promotes virus proliferation and transmission. Some patients developed multiple organ dysfunction syndromes other than lungs. Therefore, studying the viral susceptibility of other organs is important for a deeper understanding of viral pathogenesis.MethodsThe advantage of scRNA-seq … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 35 publications
0
70
0
2
Order By: Relevance
“…The serine protease TMPRSS2 on the cell surface activates the spike proteinmediated membrane fusion pathway, which is important for virus spread (Iwata-Yoshikawa et al, 2019;Zhou et al, 2015). It has been reported that TMPRSS2 is enriched in nasal and bronchial tissues (Qi et al, 2020;Sungnak et al, 2020a;Sungnak et al, 2020b), implying that the transmission of SARS-CoV-2 by respiratory droplets might be enhanced for virus bearing an intact versus a deleted S1/S2 boundary. In our hamster experiments, the deletion mutant virus Sdel exhibited decreased viral infection and disease compared to Sfull.…”
Section: Discussionmentioning
confidence: 99%
“…The serine protease TMPRSS2 on the cell surface activates the spike proteinmediated membrane fusion pathway, which is important for virus spread (Iwata-Yoshikawa et al, 2019;Zhou et al, 2015). It has been reported that TMPRSS2 is enriched in nasal and bronchial tissues (Qi et al, 2020;Sungnak et al, 2020a;Sungnak et al, 2020b), implying that the transmission of SARS-CoV-2 by respiratory droplets might be enhanced for virus bearing an intact versus a deleted S1/S2 boundary. In our hamster experiments, the deletion mutant virus Sdel exhibited decreased viral infection and disease compared to Sfull.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, expression of ACE2 and TMPRSS2 have been detected in lung airway cells and the upper respiratory epithelium, the primary site of SARS-CoV-2 action (Sungnak et al, 2020;Ziegler et al, 2020). Beyond respiratory distress, some patients with SARS-CoV-2 viremia develop multiple organ injuries, and cells of these tissues also express ACE2 and TMPRSS2 (Qi et al, 2020;Seow et al, 2020;Zou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Again similar to SARS-CoV, SARS-CoV-2 also requires the transmembrane serine protease 2 (TMPRSS2) for spike protein priming and entry into the host cell [22], although for SARS-COV-2 this might vary depending on the cell type [24,25]. Therefore, cells that express ACE2 and TMPRSS2, such as the glia and neurons, would be plausible targets for SARS-CoV-2 infection [26]. At these early stages of our understanding of COVID-19, SARS-CoV-2 infection of the CNS is speculative and, although the mechanisms of SARS-CoV-2 entry into the CNS have not yet been studied, extrapolation from closely related viruses points toward some possible routes of infection.…”
Section: Gateway To the Brain: Neurotropic And Neuroinvasive Potentiamentioning
confidence: 99%